Labour reforms in Qatar: continuity and change in perceptions and attitudes among citizens and migrant workers - Abdoulaye Diop (7117658) (2023)
Hosting the FIFA World Cup was a pivotal moment for Qatar and the broader Arab region, attracting attention, tourism, and economic benefits. However, it also intensified global scrutiny of Qatar's labor laws that govern the lives of migrant workers. In response, Qatar implemented significant labor reforms to address criticisms and enhance the business environment. Despite these efforts, ongoing evaluation is crucial for assessing reforms' effectiveness. To understand public attitudes, a 2021 nationally-representative telephone survey targeted Qatari nationals and migrant workers. The survey explored how recent employment system changes affected their lives, perceptions, and attitudes. Findings reveal the potential for substantial change, driven partly by international pressure promoting reform. Continuous research and monitoring are vital for sustaining these changes and navigating challenges. This comprehensive approach is essential for grasping the intricate dynamics shaping Qatar's evolving socio-economic landscape. Other Information Published in: Asian Population Studies License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/17441730.2023.2284017